Hydroxyamidine Hydrochloride as a Spectrophotometric Reagent for Iron(III)† - Khan, Shahbaz; Lata Mohabey, Hem (Asian Journal of Chemistry, 2010)
The preparation and properties of five new hydroxyamidine hydrochlorides have been described. Equimolar quantities of N-aryl hydroxylamine and N-aryl-imidoyl chloride were reacted in diethyl ether All the isolated compounds have been charaterised on the basis of m.p., elemental analysis, ultraviolet and infrared spectra. All the hydroxyamidines react with iron (III) forming blue alcohol soluble complex at 2.2 to 4.0 pH and above 4.5 pH colour changes to violet. In presence of thiocyanate a hyperchromic and hypsochromic effect is observed. The orange-red complex which can be extracted into benzene absorbs strongly at 460 nm. Thus a new method can be developed for extraction-spectrophotometric determination of iron(III).